Learning fluid prescription skills: why is it so challenging?. (12th May 2015) - McCloskey, Marguerite; Maxwell, Peter; Gormley, Gerry
Summary Background It is well recognised that medical students and junior doctors find fluid prescription a challenging topic. This study was designed to gain a greater understanding of the experiences that medical students face related to learning about fluid prescribing. Methods A qualitative approach, using focus groups, was employed in this research. Final‐year medical students in academic year 2011–12 at Queen's University Belfast were invited to participate during their 'Assistantship' placement in March 2012. Discussions in focus groups, consisting of between six and eight students, were recorded and transcribed verbatim. The research team, consisting of three separate investigators, conducted thematic analysis independently. A final consensus regarding emerging themes was reached by discussion within the whole research team. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Medical students and junior doctors find fluid prescription a challenging topic </boxed-text> Results Five prominent themes emerged: 'Teaching experience: a disruptive variation'; 'Curricular disconnections'; 'The driving test: Theory–practice transformation'; 'Role modelling: which standard to aspire to?'; and finally 'Reconciling the perceived risk'. Discussion This re search provided insights into medical students' opinions of the teaching practices and learning experiences related to fluid prescribing. The learning of prescribing skills is complex and contextual. In the development of such skills, medical students are often exposed to conflicting educational experiences that challenge the novice learner in making judgements on best prescribing practice. This study adds to the body of evidence that fluid prescription is a difficult topic, and has generated a number of multifaceted and strategic recommendations to potentially improve fluid prescription teaching.